La memoria, la justicia y el tiempo: una reflexión desde los derechos humanos - Casas Becerra, Lidia (2025)
The text reflects on memory as an indispensable condition for truth and justice, emphasizing that the passage of time and the death of perpetrators and victims fragment accounts and thus enable perpetrators’ “biological impunity.” It examines procedural rules that limit access to justice, illustrated by cases such as Pinochet, Ríos Montt, and Eichmann, who evaded responsibility by appealing to forgetfulness or alleged mental deterioration. The distinction between individual and collective memory is underscored: the former is unstable and subject to neurological decay; the latter, built from fragmented narratives, demands deliberate efforts to preserve it and transform it into a tool for social redress. Transitional justice cannot rely solely on courts; it requires complementary measures to uphold the duty of “non-repetition” and to provide official recognition of victims. Finally, the text warns of political denialism that trivializes or justifies past crimes and threatens to erase collective memory. It concludes that a country that forgets is doomed to repeat its past, and that preserving remembrance is, in itself, an act of justice.